Sequential high-dose cytarabine and mitoxantrone (S-HAM) versus standard double induction in acute myeloid leukemia—a phase 3 study. Issue 12 (December 2018) - Braess, Jan; Amler, Susanne; Kreuzer, Karl-Anton; Spiekermann, Karsten; Lindemann, Hans; Lengfelder, Eva; Graeven, Ullrich; Staib, Peter; Ludwig, Wolf-Dieter; Biersack, Harald; Ko, Yon-Dschun; Uppenkamp, Michael; et al.
Abstract Dose-dense induction with the S-HAM regimen was compared to standard double induction therapy in adult patients with newly diagnosed acute myeloid leukemia. Patients were centrally randomized (1:1) between S-HAM (2nd chemotherapy cycle starting on day 8 = "dose-dense") and double induction with TAD-HAM or HAM(-HAM) (2nd cycle starting on day 21 = "standard"). 387 evaluable patients were randomly assigned to S-HAM (N = 203) and to standard double induction (N = 184). The primary endpoint overall response rate (ORR) consisting of complete remission (CR) and incomplete remission (CRi ) was not significantly different (P = 0.202) between S-HAM (77%) and double induction (72%). The median overall survival was 35 months after S-HAM and 25 months after double induction (P = 0.323). Duration of critical leukopenia was significantly reduced after S-HAM (median 29 days) versus double induction (median 44 days)—P < 0.001. This translated into a significantly shortened duration of hospitalization after S-HAM (median 37 days) as compared to standard induction (median 49 days)—P < 0.001. In conclusion, dose-dense induction therapy with the S-HAM regimen shows favorable trends but no significant differences in ORR and OS compared to standard double induction. S-HAM significantly shortens critical leukopenia and the duration of hospitalization by 2 weeks.